2021
DOI: 10.22141/2224-0721.14.1.2018.127089
|View full text |Cite
|
Sign up to set email alerts
|

Взаємозв’язок Гіпотиреозу Та Андрогенного Дефіциту У Чоловіків В Різні Періоди Зрілого Віку

Abstract: Актуальність. Поєднання патології щитоподібної залози (ЩЗ) з віковим андрогенним дефіцитом у чоловіків сприяє зниженню сексуальної і репродуктивної функцій, погіршенню якості життя. Мета дослідження — виявити особливості взаємозв’язків між зниженою функцією ЩЗ та андрогенним дефіцитом у чоловіків в першому і другому періодах зрілого віку. Матеріали та методи. Під спостереженням перебувало 60 чоловіків із первинним гіпотиреозом віком від 21 до 60 років. Набір чоловіків для обстеження проводили в процесі амбулат… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In patients with DM, these disorders are complicated by hyperglycemia, as well as other biochemical disorders that occur against its background. The importance of hyperglycemia as one of the risk factors for the development of autoimmune disorders in patients with DM has been shown in many studies that have shown that maintaining strict metabolic control can normalize immunological changes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with DM, these disorders are complicated by hyperglycemia, as well as other biochemical disorders that occur against its background. The importance of hyperglycemia as one of the risk factors for the development of autoimmune disorders in patients with DM has been shown in many studies that have shown that maintaining strict metabolic control can normalize immunological changes [20,21].…”
Section: Discussionmentioning
confidence: 99%